Active Damping and Drive Train Control for a Wind Turbine with a Hydrostatic Transmission and a PMSG. Issue 1 (July 2017) - Aschemann, Harald; Kersten, Julia
Abstract: In this paper, a model-based control is proposed for an innovative 5 MW wind turbine with a hydrostatic transmission and a permanent magnet synchronous generator (PMSG). The scheme involves two decentralised controllers, one for the tower and blade deflections and another for the drive train. For an active oscillation damping of both the tower and the rotor blades, an LQR design based on Linear Matrix Inequalities (LMIs) is used so that given parameter uncertainties can be considered adequately. Here, the pitch angle serves as control input. The drive train control is given by a LQR design based on extended linearisation techniques, where the rotor angular velocity is controlled by adjusting the hydrostatic transmission. The control is capable to cover the whole operating range from low to very high wind speeds. A disturbance observer is used to estimate the aerodynamic rotor torque as well as leakage effects in the hydrostatic transmission. Hence, the estimated rotor torque can be used to reconstruct the wind speed. The overall control performance is illustrated by realistic simulation results, which show an improved damping of tower and blade oscillations and an excellent tracking behaviour.